2012
DOI: 10.1007/s10856-012-4608-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of fibroblast culture in three-dimensional activated carbon fiber-based scaffold for wound healing

Abstract: This work developed a novel bi-layer wound dressing composed of 3D activated carbon fibers that allows facilitates fibroblast cell growth and migration to a wound site for tissue reconstruction, and the gentamicin is incorporated into a poly(γ-glutamic acid)/gelatin membrane to prevent bacterial infection. In an in vitro, field emission scanning electron microscopy shows that rat skin fibroblasts appeared and spread on the surface of activated carbon fibers, and penetrated the interior and exterior of the 3D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…At day 21, re‐epithelialization in the wounds treated with SOD‐PGAS/PGA‐H was more complete than re‐epithelialization in those treated with PGAS/PGA‐H, while the surface of the wounds in control group was covered with underlying granulated tissue that had not yet epithelialized. Previously reported results have shown that appropriate inflammation is necessary for wound healing, but prolonged inflammation is detrimental to its outcome . This observation is consistent with our results, where wound healing in the test groups (PGAS/PGA‐H and SOD‐PGAS/PGA‐H), especially in the SOD‐PGAS/PGA‐H group, was faster and more complete than in the control group, probably due to the fact that wounds re‐epithelialize more rapidly under moist conditions .…”
Section: Resultsmentioning
confidence: 99%
“…At day 21, re‐epithelialization in the wounds treated with SOD‐PGAS/PGA‐H was more complete than re‐epithelialization in those treated with PGAS/PGA‐H, while the surface of the wounds in control group was covered with underlying granulated tissue that had not yet epithelialized. Previously reported results have shown that appropriate inflammation is necessary for wound healing, but prolonged inflammation is detrimental to its outcome . This observation is consistent with our results, where wound healing in the test groups (PGAS/PGA‐H and SOD‐PGAS/PGA‐H), especially in the SOD‐PGAS/PGA‐H group, was faster and more complete than in the control group, probably due to the fact that wounds re‐epithelialize more rapidly under moist conditions .…”
Section: Resultsmentioning
confidence: 99%
“…The optical density was read with a microplate spectrofluorometer (Molecular Devices SpectraMax M2 e , Sunnyvale, USA) at a wavelength of 570 nm. All experiments were performed six times with eight replicate wells for each sample and control per assay [34, 35]. …”
Section: Methodsmentioning
confidence: 99%
“…This scaffold promoted fibroblast growth and migration, leading to up-regulation of fibronectin and type I collagen, which was theorized to have allowed for accelerated wound healing and closure. [16] …”
Section: Wound Healing Productsmentioning
confidence: 99%